Desafios para a efetivação democrática do Plano Municipal de Educação no município de Toropi/RS: possíveis (re)construções nas relações teoria-prática - Oliveira, Marli Almeida de (2020)
This Professional Master's research is part of the Pedagogical Management and Educational Contexts Research Line, of the Postgraduate Program in Public Policies and Educational Management (PPPG) at the Federal University of Santa Maria (UFSM), RS. Its main goal consists in the study, debate and construction of paths and devices for the creation of an Agenda, involving teachers and school community. Such an Agenda hopes to make Democratic Management viable in the municipal education network, dialogued and participated, especially by the implementation of a goal within the Municipal Plan of Toropi/RS. For raising awareness and carrying out self-(trans)formation, we have adopted the political-epistemological proposal of the Investigative self-(trans)formative Dialogic Circles (HENZ, 2015) as a methodological path. Within a qualitative research approach, our meetings were held virtually due to the COVID-19 pandemic. After carrying individual and shared studies with co-authored teachers and mothers, we strongly believe that democratic management and permanent self-(trans)formation is not only feasible, but it also reinforces our pedagogical and political commitment as professionals in the construction of a democratic society. For the understanding and interpretation of self-(trans)formative epistemological constructs, we have opted for the philosophical hermeneutics approach. The understanding brought about by the dialogical-reflective meetings propelled us to fight for an education of social and human quality, with dialogued and participated praxis, in the service of liberation and humanization. The dialogues and systematization of the intervention construct (“final product”), have allowed us to verify that Toropi has legal regulations and regulatory milestones for the implementation of Goal 19 of its Municipal Education Plan. Consequently, this goal has the potential to make all education to be dialogued and shared with the community. Thus, the Agenda consists of proposing new paths and/or strategies for different legal instances. In order to do so, it requires the political will of the managers, as well as the interest of the society into a collective and cooperative construction. For this end, the actions should focus on the permanent self-(trans)formation with teachers, placing them as protagonists in the implementation of the democratic praxis in schools and in society.